Analisis Historis Makam Kuno: Studi Kasus Makam-Makam Kuno Islam di Kelurahan Martubung, Kecamatan Medan Labuhan - Anggraini, Mutia; Monang, Sori; Harahap, Nursapia (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article aims to make an inventory of ancient tombs in the city of Medan, especially those scattered around Neighborhoods III and V, Martubung Village, Medan Labuhan District. The strategic position of Medan City causes this region to have diversity in terms of culture and others. No exception, the typology of ancient tombs in this region is also influenced by various countries that have come into contact with this region, one of which is Aceh. This research is included in the type of field research using historical research methods. The results of this study indicate that: 1) the number of ancient tombs identified in Martubung Village are five tombs, namely: the tombs of Datuk Tongah, Datuk Payung, Datuk Hasan, Datuk Hitam and Datuk Dadih. However, only two tombs still leave historical traces in the form of tombstones, namely the tomb of Datuk Tongah and the tomb of Datuk Payung; 2) The condition of the ancient tombs in Martubung Village is currently very worrying because there are only two tombs left with cracked headstones on the body and head of the headstone; and 3) efforts to maintain ancient tombs in Martubung Village are only carried out by the surrounding community in a makeshift way without government intervention.